E-loyalty formation of Generation Z: Personal characteristics and social influences - Ranjit Singh; P.S. Sibi (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: This study examines the personal characteristics and social influence of Generation Z on their e-loyalty towards tourism websites. In contrast to previous models, this study explores the effect of perceived compatibility and innovativeness (personal characteristics) and subjective norm (social influence) on perceived usefulness and trust on tourism websites, which in turn influence e-loyalty in a generational context. These factors are crucial in e-commerce, but they have not been studied together in the context of tourism, especially for Generation Z. Methods: Using a sample size of 389 respondents falling within Generation Z in India, the proposed model was validated using PLS-SEM. A quantitative approach was followed in this study and the data was collected by using a survey questionnaire. Results: Within the wider context of technology adoption, the findings show the decisive role of both personal characteristics and social influence in determining the e-loyalty of Generation Z towards tourism websites. Implications: The implications of understanding the e-loyalty of Generation Z may assist tourism firms in retaining them by developing and implementing effective marketing strategies. Moreover, the study's most significant contribution is that it considers Generation Z, a generation that will shape the world's future economy and a digital sector with significant purchasing power and influence.
Keywords: A13; C31; L84; 330; e-loyalty; Generation Z; Perceived compatibility; Innovativeness